(3cJGH GdefJNH ef GdehGYXs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3deG cGfJ GdehGYX efOhHkG ZdgjG Hbhdg JYGdi hPcQ aEf GdPcQi JfaY GdeDefjf , hbhd GdfHi Udi Gddg Ydjg hSde (B( (3JYGgOhG GdfGS HGdJPcQ s
(3BNQgG (B:s
(3hcJH dhGFd Hf MLQ hbheg ef eMeO QShd Gddg Edi GdCbjGd GdYHGgd Cgd MVQehJ BNQ cJGH GdefJNH hGdMeO ddg OGFekG s
(3ai eGFI aUds
(3fSNI fajSI LOkGs
(3Ydi GdfSNI bQGAI deGdcgG CHj HcQ GdehUdis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs